Similarity judgements: the comparison of normative predictions and subjective evaluations – A study of the ratio model of similarity in social context - Jabłońska, Magdalena Zyta; Falkowski, Andrzej; Mackiewicz, Robert (Frontiers in Psychology, 2024)
In our study, we address two research gaps in similarity studies. First, we investigate how well subjective evaluations follow the normative models of similarity. Here, we compare the normative predictions of Tversky's ratio model with actual evaluations done by study participants about similarities of fictitious political candidates to the image of an ideal and bad politician. Second, we analyse how valence (i.e., the positivity and negativity) of target, referent and of additional features affects these similarity judgements. Our findings show that the normative model predicts well the similarity judgements of unfavourable candidate profiles but not of favourable ones. Additionally, the differences between candidates are more visible when they pertain to negative features, especially when these features are added to the descriptions of favourable candidates. Our findings add to the research on positive-negative asymmetry, differentiation processes as well as similarity and plausibility judgements.